Pengembangan E-Modul Berbasis Etnofisika Pada Materi Gelombang Bunyi - Humaira, Siti; Ngadimin, Ngadimin; Wahyuni, Agus; Nurulwati, Nurulwati; Musdar, Musdar (EduFisika: Jurnal Pendidikan Fisika, 2025)
Physics education in Indonesia often struggles to present abstract concepts in a way that is easily understood and engaging, leading to learning difficulties among students. Integrating ethnophysics—contextualizing physics within local cultural practices and knowledge systems—offers a promising approach, especially in culturally rich regions. Sound waves, as a fundamental topic, provide opportunities for such integration through instructional modules. This study aims to evaluate the feasibility of an ethnophysics-based electronic module (e-module) on sound wave material through a research and development (R&D) approach. The development process followed the ADDIE model, limited to the stages of analysis, design, and development, and was followed by a limited-scale trial. Data were collected using expert validation sheets and student and teacher response questionnaires. Four validators participated, comprising two subject matter experts and two media experts. The limited-scale trial was conducted with 11th-grade students (class F-6) at SMA Negeri 1 Darul Imarah, Aceh Besar. The validation results indicated high validity, with expert scores of 0.81 (subject matter) and 0.87 (media). Content validity scored 0.86, construct validity 0.85, and language validity 0.66, yielding an overall score of 0.84—classified as highly valid. Student and teacher response rates were 84.8% and 90.3%, respectively, indicating strong practicality. These findings suggest that the developed ethnophysics-based e-module is both valid and practical, with strong potential to support culturally relevant and effective physics instruction.